Modified T2FSMC approach for solar panel systems. Issue 1 (1st January 2019) - Mardlijah,; Zhai, Guisheng; Adzkiya, Dieky; Mardianto, Lutfi; Ikhwan, Muhammad
Abstract : In this paper, we consider the control problem for solar panel systems such that the panel is perpendicular to the direction of sunlight, which is suitable for absorbing the sun's energy efficiently. Based on the existing Type-2 Fuzzy Sliding Mode Control (T2FSMC) method, we propose a Modified T2FSMC approach in this paper, where a bisection algorithm is used to compute the normalized gain. According to simulation results, the performance of Modified T2FSMC is significantly better compared to the performance of T2FSMC and Fuzzy Sliding Mode Control (FSMC). Specifically, Modified T2FSMC has a smaller steady-state error and is more robust to disturbance compared with FSMC. Moreover, Modified T2FSMC also has a smaller steady-state error compared to T2FSMC.